Comparative Effects of Telmisartan versus Valsartan on serum Leptin level, in hypertensive type 2 diabetes mellitus patients - Najlaa Saadi Ismael; Fathel Abaas Al-hamamy (University of Mosul, 2019)
Objective: The aim of this study was to compare the effects of telmisartan and valsartan onblood pressure and serum leptin in hypertensive type 2 diabetesMellitus patients. Study design:A randomized control comparative clinical trial with open label design. Study period: From 1st  February, 2012 to 30th March, 2013. Patients and method: Eighty eight type 2 diabetic hypertensive  patients were randomly assigned to received either telmisartan (n = 46)  or valsartan (n = 42) with body mass index (BMI) 31.52±4.73 kg/m², 30.39±3.95 kg/m² respectivly. Forty one diabetic normotensive patients (n=41), age, sex, BMI, duration of diabetic  disease, duration of diabetic treatment matched to the diabetic hypertensive  patients groups were kept as control group. blood pressure (BP), leptin levels were measured at baseline and after 2 months of treatment. Results: The study showed a significant higher systolic blood pressure (SBP), diastolic blood pressure (DBP) and serum leptin in the diabetic hypertensive patients before starting therapy as compared with the diabetic normotensive patients. Both telmisartan and valsartan significantly reduced serum leptin and BP. More reduction in DBP seen with valsartan  than with telmisartan. Conclusion: Monotherapy with telmisartan and valsartan produce a beneficial reduction effects on BP and reduce leptin level. The improvement of leptin sensitivity may play a role directly or indirectly in the induction of hypertension control.